Identification of Pests and Diseases of Calathea Ornamental Plants in Ngledoksari Village, Karanganyar - Hanik, Nur Rokhimah; Cahyanti, Fiky Ariska; Wahyuni, Tri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Maintaining ornamental plants is a hobby that many people do as a refreshing activity. One type of ornamental plant is calathea, which is an ornamental plant that has many leaves and attractive patterns. Because there are so many people interested in calathea ornamental plants, care is needed that can produce optimal growth of calathea so that it has a high selling value. Calathea with high sales value usually has a combination of several factors, including the uniqueness of the variety, the beauty of the leaves, the health of the plant, and the level of difficulty in maintaining it. The aim of this research is to determine pests and diseases on Calathea ornamental plants in Ngledok Sari Village, Karangayar. The method used is observation and interviews with sources who are considered competent in their fields. The research results identified snail/snail pests, Paracoccus marginatus (mealybugs), caterpillars, spider mites, and grasshoppers as well as diseases including chlorosis/nutrient deficiencies and leaf burns due to direct sunlight which were documented in 22 photo samples. It is hoped that this research can be used as a reference source and studies for further research.